1996
DOI: 10.1002/(sici)1096-9071(199604)48:4<339::aid-jmv7>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C plasma viral load is associated with HCV genotype but not with HIV coinfection

Abstract: The influence of human immunodeficiency virus (HIV) coinfection and hepatitis C virus (HCV) genotype distribution on HCV viral load and alanine amino transferase (ALT) levels in chronically infected patients remains unclear. In the present study, serum samples from a group of haemophiliac patients were investigated retrospectively. HCV geno- and subtyping was carried out using the Inno line probe assay (Inno LIPA, Innogenetics, Zwijnaarde, Belgium) in 87 patients positive by HCV RT PCR. Of these patients, 31 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
1
15
1
Order By: Relevance
“…Our results are in conflict with other studies in coinfected patients, which have shown an association between genotype 1 infection and increased quasispecies diversity (38) and HCV load (1,49). However, none of these studies stratified patients based on exposure to HAART.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in conflict with other studies in coinfected patients, which have shown an association between genotype 1 infection and increased quasispecies diversity (38) and HCV load (1,49). However, none of these studies stratified patients based on exposure to HAART.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have shown that genotype 1b infection of HCV in male subjects was significantly associated with higher viral loads (Lee et al, 2006;Yu et al, 1999). There were significant differences in virus load associated with infection with different genotypes of HCV (Berger et al, 1996;Chan et al, 1995;Lu et al, 1998;Mahaney et al, 1994;Matsumoto et al, 1994;Orito et al, 1994;Yamada et al, 1995). Our finding that HCV RNA levels in the specimens with genotypes 6a or 1a/1b were significantly higher than those positive for genotype 3b provides a possible mechanism for the higher prevalence of HCV infection with genotypes (6a, or 1a/1b) among the subjects of this study.…”
Section: And 6lvn530 (D88471)mentioning
confidence: 99%
“…In contrast, others (1,3,11,29) report worsened histopathology and increased frequency of hepatic decompensation with decreased CD4 counts. Furthermore, some investigators report an inverse correlation between HCV RNA load and CD4 T-cell count (2,11,13,15), whereas others have found no such correlation (4,6,7,26,33,38,39,40).…”
mentioning
confidence: 99%
“…Additional potential correlates of HCV load, e.g., alanine aminotransferase (ALT) level, aspartate aminotransferase (AST) level, age, race, sex, HCV genotype, hepatitis B surface antigen (HBsAg) positivity, duration of infection, mode of infection, and HIV load, have been investigated, with various results (4,8,15,18,25,36,39,40). These discrepant findings reflect the difficulty of understanding a disease for which both the initial time of infection is often unknown and the course is characterized by a prolonged asymptomatic period.…”
mentioning
confidence: 99%